O saneamento rural e suas implicações nas relações de gênero : um estudo em três localidades brasileiras - Bárbarah Brenda Silva Rocha (2022)
Water and sanitary exclusion affects a significant portion of the Brazilian population, especially in rural areas and on the outskirts of cities. In view of the role socially assigned to women, it is imperative to adopt a gender perspective in public water and sanitation policies and in health solutions aimed at the population, which seek answers to the structural causes of health exclusion and are capable of publicizing this adverse situation and encourage discussions that promote the rupture of culturally established patterns that penalize women. Thus, the relevance of this research is inserted in the contribution to confronting gender inequalities in water supply and sanitary, due to its innovative character when anchored in theoretical foundations belonging to different fields of knowledge. Bearing in mind the theoretical gaps inherent to the theme and the current state of the art that surrounds it, the general objective of this thesis is to analyze how gender inequalities are manifested in the strategies adopted in water supply and sanitary sewage, in rural households in Brazil. For that, a qualitative methodology is used, through semi-structured interviews, direct observation and thematic-categorical analysis. The empirical reference of this research included three Brazilian rural communities: Barreiro Amarelo and Nova Esperança, in Bahia, and the Settlement Pontal do Buriti, in Goiás. This research adopts the feminist line, assuming as theoretical-methodological references the studies on contemporary patriarchy and the sexual division of labor. The results suggest that, based on the patriarchal organizational logic of rural areas, women and men have dichotomous and exclusive spheres of action. Women are responsible for private, reproductive and non-remunerated tasks, thus assuming the management of water and sanitation at home. Faced with the sexual division of labor, it was found that such dedication is made invisible, not financially and socially valued, and causes greater burden and negative effects on women's lives. The more precarious the water and sanitary solution, bigger is the level of stress, overload, tiredness and illness of women. The influence of mass traditions and behaviors, which reproduce the dominant culture, on the division of labor places women at a disadvantage and greater vulnerability in relation to men. In these terms, the paradigm that shapes the sexual division of labor in the families of the studied communities reinforces gender inequalities. Changing this situation will require transversal and correlated public policies, supported by scientific studies, and that consider feminist theories in identifying and overcoming situations that lead to gender inequalities.